Intergenerational effects of dietary iron on swimming and metabolic performance in zebrafish - Chandrapalan, Theanuga; Walia, Suhani; Kwong, Raymond W. M. (Frontiers in Physiology, 2025)
Iron is an essential trace metal required for various physiological processes, yet both deficiency and excess can disrupt metal homeostasis and compromise fitness. In this study, we investigated how dietary iron availability influences physiological performance across generations in zebrafish (Danio rerio). Fish were fed diets spanning a gradient from deficiency to supplementation (Low Fe, 11 mg Fe/kg; Medium Fe, 420 mg Fe/kg, and High Fe, 2,300 mg Fe/kg), and effects on growth, metal homeostasis, swimming performance, energy metabolism, and reproduction were assessed. Following reproductive assays, offspring were raised under control conditions and subsequently challenged with the same dietary iron treatments (Low Fe, Medium Fe, and High Fe as parents) in adulthood. Sub-acute exposure (20 days) to elevated dietary iron enhanced aerobic scope, maximum metabolic rate, and critical swimming speed, alongside improved reproductive output as measured by embryo survival and early development. However, sub-chronic exposure (40 days) to High Fe diminished swimming performance benefits and was also associated with tissue iron loading. Notably, zebrafish tolerated sub-chronic exposure to Low Fe without significant impacts on condition factor or energetic performance. Interestingly, the difference in swimming and metabolic performance between high and low iron treatments was more pronounced in the offspring, suggesting an intergenerational effect of parental iron status. Together, these findings suggest that dietary iron availability can shape both immediate and inherited performance phenotypes, underscoring its dual role as a nutritional requirement and a regulator of ecological fitness.